The impact of minority extremism on Islamic economics in multicultural Indonesia - Sarpini, Sarpini; Mawardi, Kholid (Journal of Islamic Economics Management and Business (JIEMB), 2023)
Indonesia, characterized by its rich cultural diversity, faces significant challenges from transnational extremist movements that threaten its harmonious coexistence. This study investigates the impact of minority extremism within a multicultural society on the development and implementation of Islamic economics in Indonesia. Using qualitative methods, the research collects descriptive data through observations and secondary sources, including documents, journals, and previous studies. Findings reveal that minority extremism disrupts the objectives of Islamic economics, which aims to balance material prosperity with spiritual well-being. Extremist ideologies, often lacking nationalism and intolerant of non-Islamic elements, hinder Indonesia’s goal to become a leading center of Islamic economics by 2024. These movements undermine national unity and pose significant challenges to achieving the economic, social, and spiritual goals outlined in the maqāṣid sharia. The study underscores the critical need for fostering tolerance and inclusivity to protect and promote Islamic economics in a multicultural society. Addressing the ideological roots of extremism is essential for safeguarding Indonesia's diverse and harmonious societal fabric. This research contributes to policy discussions on strengthening the resilience of Islamic economic frameworks against extremist threats, emphasizing the importance of maintaining unity and promoting inclusive growth.